Information security--the next decade : proceedings of the IFIP TC11 Eleventh International Conference on Information Security, IFIP/Sec '95 - Eloff, Jan H. P.; Von Solms, Sebastiaan H. (Chapman & Hall on behalf of the IFIP, 1995)
This books presents a tate-of-the-art review of current perspectives on information security. It contains the selected proceedings of the Eleventh International Information Federation for Information Processing and held in Cape Town, South Africa, May 1995. Information Security examines the information security requirements of the next decade from both research, industrial and practical viewpoints. Some of the major topics discussed include: information security and business applications, information security standards, management of information security, crytography, key management schemes and mobile computing, information security and groupware, building secure applications, open distributed security, management of information security, open distributed security, information security and business applications, access control, legal, ethical and social issues of information security.